Emanzipatorisches Wohnen Myra Warhaftigs Beitrag zur Internationalen Bauausstellung 1984/87 - Krüger, Anna (KIT Scientific Publishing, 2022)
This monograph illuminates Myra Warhaftig's (1930-2008) architectural contribution to the 1984/87 International Building Exhibition in Berlin. The focus is on the life and work of a Jewish female architect in Germany, in which scientific, social and ethical demands are uniquely combined.